Recent insights on pattern recognition receptors and the interplay of innate immune responses against West Nile Virus infection - Behari J.; Yadav K.; Khare P.; Kumar B.; Kushwaha A.K. (My University, 2025)
The recent outbreaks of neurotropic West Nile Virus (WNV) in humans are of grave public health concern, requiring a thorough understanding of the host immune response to develop effective therapeutic interventions. Innate immunity contributes to the primary immune response against WNV infection aimed at controlling and eliminating the virus from the body. As soon as WNV infects the body, pattern recognition receptors (PRRs) recognize viral pathogen-associated molecular patterns, particularly viral RNA, and initiate innate immune responses. This review explores the diverse PRRs in sensing WNV infection and orchestrating immune defenses. Specifically, this paper reviews the role of PRRs in WNV infection, encompassing both findings from mouse models and current clinical studies. Activation of PRRs triggers signaling pathways that induce the expression of antiviral proteins to inhibit viral replication. Understanding the intricacies of the immune response is crucial for developing effective vaccines and therapeutic interventions against WNV infection. © 2024 Elsevier Inc.